2010
DOI: 10.1007/s10546-010-9476-1
|View full text |Cite
|
Sign up to set email alerts
|

Dew Formation, Eddy-Correlation Latent Heat Fluxes, and the Surface Energy Imbalance at Cabauw During Stable Conditions

Abstract: Observations collected between 2000 and 2008 at the Cabauw meteorological measurement platform in the Netherlands were conditionally sampled to select nights with stably stratified atmospheric conditions, clear skies and weak horizontal wind speeds (<3 m s −1 ). For these conditions the eddy-correlation latent heat fluxes are found to be negligibly small, while the conditionally sampled surface energy balance exhibits a maximum residual. However, inspection of the specific humidities for these conditions revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Upward radiation fluxes are derived from older instruments having somewhat higher uncertainties: 2 % for shortwave and 5 W m −2 for longwave radiation. Failure in closing the surface energy budget from micrometeorological observations (Oncley et al 2007;Foken 2008 andRoode et al 2010) forces us to attribute a large uncertainty to the observed surface heat fluxes. For daytime, the uncertainty is typically 10-15 % of the available energy.…”
Section: Models and Observationsmentioning
confidence: 99%
“…Upward radiation fluxes are derived from older instruments having somewhat higher uncertainties: 2 % for shortwave and 5 W m −2 for longwave radiation. Failure in closing the surface energy budget from micrometeorological observations (Oncley et al 2007;Foken 2008 andRoode et al 2010) forces us to attribute a large uncertainty to the observed surface heat fluxes. For daytime, the uncertainty is typically 10-15 % of the available energy.…”
Section: Models and Observationsmentioning
confidence: 99%
“…ET act estimated with this method was on average 4 % higher than ET pot during well-watered conditions (meaning that the storage deficit was below 100 mm). Overestimation of the daily evapotranspiration sum may be caused by an underestimation of dew formation at night (De Roode et al, 2010). As a quick fix, we divided ET act by 1.04.…”
Section: C Brauer Et Al: Application Of Walrus To Two Contrastinmentioning
confidence: 99%
“…The eddy covariance water vapor flux was biased low in saturation conditions because of the poor frequency response of its open-path analyzer (Roode et al 2010). To circumvent the problem, we used the gradient diffusion method to determine the water vapor flux above the canopy.…”
Section: Nighttime Water Vapor Flux Under Saturation Conditionsmentioning
confidence: 99%